Understanding Self-Awareness and Its Impact on Job Interview Performance: A Qualitative Study on Candidate Reflection, Stress Management, and Employability Outcomes - Sudarmi, Elisabeth; Sunaryo, Widodo (Yayasan Sinergi Kawula Muda, 2024)
Job interviews are critical in determining candidates' employment success, with self-awareness playing a significant role in interview performance. This study explores the influence of self-awareness on successful and unsuccessful job interview candidates through a qualitative case study approach. In-depth interviews were conducted with ten participants—five successful and five unsuccessful job candidates—to analyze their preparation strategies, self-reflection, and communication techniques. Thematic analysis revealed that successful candidates exhibited a higher level of self-awareness, enabling them to confidently articulate their skills, address weaknesses constructively, and adapt to interview dynamics. Conversely, unsuccessful candidates displayed lower self-awareness, leading to difficulties in self-expression, ineffective communication, and a lack of structured responses. The findings underscore the necessity of incorporating self-awareness training in job preparation programs to improve employability outcomes. This study contributes to the growing discourse on emotional intelligence and career readiness by emphasizing self-awareness as a pivotal factor in professional success. Future research should examine the effectiveness of self-awareness interventions across various career sectors to determine their broader applicability.